Energy Mapping Approach for QoS in MANETs - Vijay Kumar, Bura; Aluvala, Srinivas; Sangameshwar, K (International Journal of Computer Sciences and Engineering, 2025)
The mobile ad-hoc networks are the mobile wireless networks which have no fixed infrastructure and routers, each node act as a router such that the end to end quality of service (QoS) is unpredictable or the single node. The end to end quality of service metrics is not changeable or fixed when the mobile networks have seen in the whole formed by combining several different nodes. Logical time (coherence time) is the time taken to send the information or a file to all the nodes is max and the end to end quality of service metrics is constant. The spreading period is the area covered or extended over a wide area over a period of time, it’s the time duration to send the information or file to the mobile network of the individual nodes. If found that the logical time is more than the spreading period the quality of service metrics is followed a particular path. The objective of this paper is to calculate or measure the end to end quality of service of each node in a mobile network and describe how energy map is constructed in a mobile wireless network.